(SFLVAD]DJ VXJP RLMRPROLMJ X]P OFXAZRU]Ps - (SVga(Sosuga(Smrw Fygacc(Sfnrws ((SA(B.(SVxga(Sorynjw(B,s, 2001)
(SOFXAZRUFV MAL RLMRPROLA IJXJVJ(B, (SSURVZRUA MAL FNAVXLMRXJXFV OFXAZRULM]P YSJUFVL]P XR AOFVR MRVXRV SAUAD]DJV FQ]XFULMR J MRLP]PLMR MRVXRV SAUAD]DJV XLORNRDJVJ OFXAZRULM]P YSJUFVL]Ps
(SOFXAZRUFV MAL RLMRPROLA IJXJVJ(B, (SSURVZRUA MAL FNAVXLMRXJXFV OFXAZRULM]P YSJUFVL]P XR AOFVR MRVXRV SAUAD]DJV FQ]XFULMR J MRLP]PLMR MRVXRV SAUAD]DJV XLORNRDJVJ OFXAZRULM]P YSJUFVL]Ps